Arabic Learning Design Using an Alef Education Platform-Based Blended Learning Model Jared M. Carman Perspective - Noor Zinatul Hamidah; Primasti Nur Yusrin Hidayanti; Abdul Wahab Rosyidi; Muhammad Ghafar; Aulia Humaira (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2024)
The aim of this research was to design a blended learning model using the Alef Education Platform based on the perspective of Jared M. Carman. The type of research approach in this study is a qualitative approach through literature review. This study classifies data based on the research areas examined by the researcher, which are related to the blended learning model and the Alef Education platform. The results of the research showed that the blended learning model learning design based on the Alef Education platform is Jared M. Carman's perspective, placing five keys to the blended learning model, namely: 1) Live events: namely initial orientation regarding objectives, material, time, learning steps, and the learning system that will be implemented. implemented, 2) Self-paced learning: After learning in class is finished, students can continue the material online at home according to predetermined targets. 3) Collaboration: Apart from using the Alef education platform, teachers can also use social media, 4) Assessment: In the case of assessments using blended learning, teachers can combine several types of assessments carried out online and offline. 5) Performance support materials: The supporting teaching materials used in blended learning here, the main thing is to use the Alef Education platform. Apart from that, teachers can also use other teaching materials for maximum learning results, such as books or other media that can support the learning process.